2013
DOI: 10.2495/sc130051
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the potentialities of urban space in Putrajaya

Abstract: In 1995, Malaysia embarked on a project to build the new federal government administrative city, Putrajaya. The city will be exemplary of a tropical city that will eventually become the model for new green cities in Malaysia. Initially, the focus was only on projecting a powerful image by desired physical and spatial structure through the macro scale scope of the master plan. On the ground, the completed parcels of the various precincts have not achieved the expected image of a Garden City mainly due to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Under Act 536, the PJj plays an important role as the local and planning authority for Putrajaya. Norhisham et al (2013) reported that Putrajaya Holdings, a government-listed company, was established to be the master developer of the city, translating philosophy between building form and landscape under the man-God-nature relationship. This green city is home to elegant and unique architecture, located in West-Central of Peninsular Malaysia, 25km South of…”
Section: Putrajaya and Iskandar Puterimentioning
confidence: 99%
“…Under Act 536, the PJj plays an important role as the local and planning authority for Putrajaya. Norhisham et al (2013) reported that Putrajaya Holdings, a government-listed company, was established to be the master developer of the city, translating philosophy between building form and landscape under the man-God-nature relationship. This green city is home to elegant and unique architecture, located in West-Central of Peninsular Malaysia, 25km South of…”
Section: Putrajaya and Iskandar Puterimentioning
confidence: 99%